Reconstruction of inclined air showers detected with the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Ahlers, M.; Ahn, E. J.; Allekotte, Ingomar; Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; Dova, Maria Teresa; Etchegoyen, Alberto; et al. (Iop Publishing, 2014)
Fil: Aab, A.. Università dell; Italia